Legal Reforms in Indonesia’s Financial Sector on Institutional Relations between Bank Indonesia and the Government - Wardhono, R. Dwi Tjahja K.; Simatupang, Dian Puji Nugraha; Shalehanti, Nadhia (Faculty of Law, Hasanuddin University, 2025)
Legal reform in the financial sector has an important role to play in preparing Indonesia a Golden Indonesia in 2045. The financial sector is very important strategic in the development and welfare Indonesia, supporting its sustainable economic development. Strengthening institutional functions and tasks as well as coordination among ministries and institutions, in this case between the central bank and the government, are essential in order to increase financial system resilience and economic growth. This study analyses financial sector legal reforms that impact institutional relations between central banks and governments by conducting comparative studies of the United States, Japan, Australia, and Thailand. This research also has been updated to present the implications of legal reform in the financial sector on Bank Indonesia's expanding duties and authorities to support a sustainable economy through the enactment of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector. The results of this study show that with the legal reform in the financial sector, there is a new perspective related to Bank Indonesia's independence, which has been adjusted through the adoption of a policy mix prioritising monetary policy. Fiscal authority does not become superior but accommodative as long as it does not conflict with monetary policy interests. The institutional relationship between Bank Indonesia and the government using a policy mix pattern that emphasizes aspects of monetary policy harmonization based on other policy paradigms that are in line with safeguarding broader economic interests.